2021
DOI: 10.1101/2021.10.23.465563
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diverse northern Asian and Jomon-related genetic structure discovered among socially complex Three Kingdoms period Gaya region Koreans

Abstract: The genetic history of prehistoric and protohistoric Korean populations is not well understood due to the lack of ancient Korean genomes. Here, we report the first paleogenomic data from Korea; eight shotgun-sequenced genomes (0.7X~6.1X coverage) from two archeological sites in Gimhae: Yuha-ri shell mound and Daesung-dong tumuli, the most important funerary complex of the Gaya confederacy. All eight individuals are from the Korean Three Kingdoms period (4th-7th century CE), during which there is archaeological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 78 publications
(72 reference statements)
0
2
1
Order By: Relevance
“…We find that the Gunsan jar coffin individuals, present-day Koreans, and various ancient groups from northern China are adequately positioned along the genetic north-south cline in East Asia, within the range defined by the following two populations: i) Bronze Age individuals from the Longtoushan archaeological site of the West Liao River region in the Upper Xiajiadian culture context (“WLR_BA”) as a genetic northern proxy, and ii) Late Neolithic individuals from the Xitoucun site in southern China (“Xitoucun”) as a genetic southern proxy (Figure 5; Table S5A). In both ancient and present-day Koreans, we do not detect a statistically significant contribution from the Jomon hunter-gatherer gene pool of the Japanese archipelago (Table S5A), although previous studies report occasional presence of the Jomon ancestry contribution from Neolithic to the early Medieval period (Gelabert et al, 2021; Robbeets et al, 2021). When we replace the genetic northern proxy from WLR_BA to Middle Neolithic individuals from the Miaogizou site in Inner Mongolia (“Miaozigou_MN”), we detect a small but significant amount of Jomon contribution in the Gunsan individuals and present-day Ulsan Koreans (3.1-4.4%; Table S5B).…”
Section: Resultscontrasting
confidence: 81%
See 1 more Smart Citation
“…We find that the Gunsan jar coffin individuals, present-day Koreans, and various ancient groups from northern China are adequately positioned along the genetic north-south cline in East Asia, within the range defined by the following two populations: i) Bronze Age individuals from the Longtoushan archaeological site of the West Liao River region in the Upper Xiajiadian culture context (“WLR_BA”) as a genetic northern proxy, and ii) Late Neolithic individuals from the Xitoucun site in southern China (“Xitoucun”) as a genetic southern proxy (Figure 5; Table S5A). In both ancient and present-day Koreans, we do not detect a statistically significant contribution from the Jomon hunter-gatherer gene pool of the Japanese archipelago (Table S5A), although previous studies report occasional presence of the Jomon ancestry contribution from Neolithic to the early Medieval period (Gelabert et al, 2021; Robbeets et al, 2021). When we replace the genetic northern proxy from WLR_BA to Middle Neolithic individuals from the Miaogizou site in Inner Mongolia (“Miaozigou_MN”), we detect a small but significant amount of Jomon contribution in the Gunsan individuals and present-day Ulsan Koreans (3.1-4.4%; Table S5B).…”
Section: Resultscontrasting
confidence: 81%
“…However, this does not imply a complete genetic isolation of the Korean population from their neighbors over the last two millennia. On the contrary, there are a growing body of genetic evidence supporting high connectivity between proto-historic Korea and its neighboring regions: a recent study reported a few early Medieval individuals with a substantial level of the Jomon ancestry from the Japanese archipelago (Gelabert et al, 2021), suggesting a vibrant international network supporting movements of people and goods. Furthermore, Kofun-period individuals from Japan suggests a continued gene flow from the continental East Asia with the Korean peninsula as a highly likely source region (Cooke et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These data are being analyzed mainly by linear algebraic methods, such as Genome Wide Association Studies (GWAS), and are beginning to reveal genomic characteristics in European populations and details of human inter-and intra-regional migrations from the past to the present [7]. Recently, studies have been conducted not only in Europe but also in East Asian populations such as Japanese, Chinese, and Korean populations [8][9][10][11][12][13].…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%